2002
DOI: 10.1080/13547500110118184
|View full text |Cite
|
Sign up to set email alerts
|

Breath biomarkers for detection of human liver diseases: preliminary study

Abstract: Chronic liver disease is initially occult, has multiple aetiologies, involves complex diagnostic questions, and requires follow-up because progression is likely. Blood tests and biopsies are generally used, but have disadvantages. We have developed a new test for liver disease based on abnormal concentrations of metabolic products detected in exhaled breath. This test can be used, in conjunction with other clinically accepted diagnostic protocols, to detect and classify chronic liver diseases. Samples of breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 30 publications
1
73
0
1
Order By: Relevance
“…It has previously been shown that both oral and gut bacteria may be significant sources of the volatile sulfur species in breath (44). Moreover, specific sulfur compounds such as carbonyl sulfide and dimethyl sulfide are known markers of liver disease pathogenesis and carbonyl sulfide has been suggested to be an early marker of acute rejection in lung transplant patients (37,43). Because the profile for the total sulfur-containing compounds tracked end-tidal carbon dioxide output, these molecules are probably generated systemically and not derived from the mouth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that both oral and gut bacteria may be significant sources of the volatile sulfur species in breath (44). Moreover, specific sulfur compounds such as carbonyl sulfide and dimethyl sulfide are known markers of liver disease pathogenesis and carbonyl sulfide has been suggested to be an early marker of acute rejection in lung transplant patients (37,43). Because the profile for the total sulfur-containing compounds tracked end-tidal carbon dioxide output, these molecules are probably generated systemically and not derived from the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a new protocol has also been developed for the analysis of total volatile sulfur-containing molecules in exhaled breath. Sulfur-containing molecules have been identified as breath markers of liver pathogenesis, lung transplant rejection, colonic fermentation, and nutrient disposition (20,37,43,44).…”
mentioning
confidence: 99%
“…COS is the only volatile sulfur that is increased in exhaled air of patients with cystic fibrosis (69) or of lung transplant patients during the acute rejection phase (150). COS is also exhaled by patients with chronic liver disease (135). COS has been demonstrated to be produced by porcine coronary arteries in vitro, and the rate of COS production is enhanced by stimulating the vessels with ACh or the calcium ionophore, A23187 (7).…”
Section: Other Potential Biosynthetic Pathwaysmentioning
confidence: 99%
“…Exhaled human breath is a complex gas mixture containing hundreds of different species [47][48][49][50]. The most prominent ones are nitrogen, oxygen, carbon dioxide and water vapor, yet there are traces of numerous other gases and volatile organic compounds (VOCs) present.…”
Section: Breath Analysismentioning
confidence: 99%